Designing Pension Plans According to Consumption-Savings Theory - Schlafmann, Kathrin; Setty, Ofer; Vestman, Roine (Review of Financial Studies, 2026)
Abstract We derive optimal characteristics of contribution rates into defined contribution pension plans based on consumption-savings theory. Contribution rates should increase with age and decrease with the balance-to-income ratio. Using Swedish registry data, we show that on average, individuals save according to those principles. However, almost half of the population behaves hand-to-mouth and does not undo the mandated constant contribution rates. In a quantitative model, designing contribution rates to follow the principles implies a 1.8% welfare gain and less dispersed replacement rates, while maintaining the same average replacement rate. Results are robust to various sources of model misspecification, including temptation preferences.